Beispiel Nr: 03
$\text{Gegeben:}\\ \text{Bruch1: }a\dfrac{b}{c} \\ \text{Bruch2: }d\dfrac{e}{f} \\ \\ \text{Gesucht:} \\\text{Summe,Differenz,Produkt,Quotient} \\ a\frac{b}{c}- d\frac{e}{f}\\ \textbf{Gegeben:} \\ a=1 \qquad b=2 \qquad c=3 \qquad d=3 \qquad e=2 \qquad f=5\\ \\ \textbf{Rechnung:} \\\text{Hauptnenner: kgV( }3,5 \text{) }= 15 \\ \text{Erweiterungsfaktoren: }\frac{15}{3}=5 \qquad \frac{15}{5}=3 \\ \\\text{Summe}\\1\frac{2}{3}+3\frac{2}{5}=1+3+\frac{2\cdot5}{3\cdot5}+\frac{2\cdot3}{5\cdot3}= 4+\frac{10+6}{15}=4+\frac{16}{15}=5\frac{1}{15} \\ \\\text{Differenz}\\1\frac{2}{3}-3\frac{2}{5}=1-3+\frac{2\cdot5}{3\cdot5}-\frac{2\cdot3}{5\cdot3}= -2+\frac{10-6}{15}=-2+\frac{4}{15}=-1\frac{11}{15} \\ \\\text{Produkt} \\ 1\frac{2}{3}\cdot 3\frac{2}{5}=\frac{1\cdot 3 +2}{3}\cdot \frac{3\cdot 5+ 2}{5}=\frac{5}{3}\cdot \frac{17}{5}=\frac{5\cdot17}{3\cdot5}= \frac{85}{15}=5\frac{2}{3} \\ \\\text{Quotient} \\ 1\frac{2}{3}:3\frac{2}{5}=\frac{1\cdot 3 +2}{3} :\frac{3\cdot 5+ 2}{5}=\frac{5}{3} :\frac{17}{5}= \frac{5}{3} \cdot \frac{5}{17}= \frac{25}{51}=\frac{25}{51} \\ $